Isolated external iliac artery aneurysm in a patient without any concomitant vascular disease - Patrick D. Conroy, MD; Jennifer Li, MD; Allen Hamdan, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Iliac artery aneurysms commonly present in patients with associated aortic disease. Isolated aneurysms of the iliac arteries are uncommon, mostly involving the common iliac artery. Isolated external iliac artery aneurysms are the rarest iliac aneurysmal pathology. We present the case of an asymptomatic isolated external iliac artery aneurysm with no other concomitant vascular disease in a middle-aged man, treated with a stent graft.